Inspiring active learning : a handbook for teachers - Harmin, Merrill (Alexandria, Va. : Association for Supervision and Curriculum Development, 1994)
Presents strategies to motivate students to learn. Centered on mutual respect, collaboration, and commitment to learning, each strategy is described and illustrated by examples which can be used by educators for all ability and grade levels.
Includes bibliographical references (p. 184-192) and index.
Professional
Keywords: Active learning -- Handbooks, manuals, etc; Motivation in education -- Handbooks, manuals, etc; Teaching -- Handbooks, manuals, etc; Learning and scholarship; Motivation (Psychology).; Teaching -- Handbooks, manuals, etc